Gypsy transposition correlates with the production of a retroviral envelope-like protein under the tissue-specific control of the Drosophila flamenco gene. - Pélisson, A (1994)
Gypsy displays striking similarities to vertebrate retroviruses, including the presence of a yet uncharacterized additional open reading frame (ORF3) and the recent evidence for infectivity. It is mobilized with high frequency in the germline of the progeny of females homozygous for the flamenco permissive mutation. We report the characterization of a gypsy subgenomic ORF3 RNA encoding typical retroviral envelope proteins. In females, env expression is strongly repressed by one copy of the non-permissive allele of flamenco. A less dramatic reduction in the accumulation of other transcripts and retrotranscripts is also observed. These effects correlate well with the inhibition of gypsy transposition in the progeny of these females, and are therefore likely to be responsible for this phenomenon. The effects of flamenco on gypsy expression are apparently restricted to the somatic follicle cells that surround the maternal germline. Moreover, permissive follicle cells display a typically polarized distribution of gypsy RNAs and envelope proteins, both being mainly accumulated at the apical pole, close to the oocyte. We propose a model suggesting that gypsy germinal transposition might occur only in individuals that have maternally inherited enveloped gypsy particles due to infection of the maternal germline by the soma.